Caracterização de fitoterápicos e plantas medicinais consumidos por pacientes oncológicos assistidos em um hospital escola - SOUSA, Larissa Beatriz Vasconcelos (2023)
Introduction: The use of medicinal plants is a therapeutic practice called phytot herapy, which is included in health care. The community of oncological patients has shown an increase in the search for alternative therapies not only for the cure of symptoms and tumors but also for their general wellbeing. However, the use of those plants may present a risk due to interactions not yet fully known with conventional antineoplastic therapy. Objective: To characterize the consumption of medicinal plants and medical phytotherapeutic in oncological patients attended at University Hospital João de Barros Barretos (HUJBB) in Belém-PA. Material and Methods: It was a descriptive, observational, sectional and quantitative study, conducted between April and May 2019 at the Oncology Care Unit of the Hospital located in Belém, Pará, Brazil. An adapted questionnaire adapted from Vieira (2008) was used, allowing the patients to cite up to 4 herbal medicines. Results: A total of 31 patients were interviewed which 58.06% were female. Fiftyfour plants of 19 different species were consumed. The species with the largest sample number were Pimpinella anisum (14.8%), Annona muricata (14.8%), Melissa officinalis (12.96%) and Peumus boldus (9.25%). Approximately 58% of patients believe in the ability of medicinal plants to assist in oncological treatment. The main reasons for use were the relief of gastric symptoms (35.18%) and antineoplastic function (24.07%). Seventyfour percent of the patients reported an improvement in their condition according to their expectations regarding the reason for the use of medicinal plants. Conclusion: Through this study, it was possible to conclude that there's a high prevalence of risk factors capable of interfering in patients' quality of life, such as monthly family income and school level. The prevalence of reasons for use shows that the treatment of gastrointestinal symptoms and antineoplastic function demonstrated a way to know the public according to their interests. Because the results presented scattered values of the medicinal plants consumed, it's necessary to develop further investigations in order to identify the true role of phytotherapy in the health of cancer patients.